Minimalisasi Masalah Agency Melalui Screening Adverse Selection dalam Pembiayaan Mudarabah di Bank Syari’ah - Muhamad Muhamad (Universitas Darussalam Gontor, 2010)
This paper attempts to theorise the behaviour of the Islamic firm in the light of the new theory of the firm. In this papers, we explore the agency problems and effort to minimalize the agency problems throught screening of adverse selection. The adverse selection due to the pre-contractual endowment of information to the entrepreneur about the productivity of the venture with respect to effort and capital. The agency problem will not happened in the mudarabah financing if the shahibul mal applied the restricted screening of adverse selection to the mudharib. The study has found that there are six attributes considered from the mudarabah projects point of view, which include the prospect of project, availability of collateral, healthiness of project, project’s financial statements, clarity of contract conditions, and conformity of time period. In regard to mudharib attributes, the study has also concluded five characteristics which are considered important. They include the business capacity, [personal] collateral, mudharibs’ reputation and family background, and their business commitments.